After we collided [videorecording (DVD)] - Sprouse, Dylan, 1992-; Langford, Josephine, 1997-; Fiennes-Tiffin, Hero; Lombard, Louise, 1970- (Voltage Pictures, 2021)
Hardin will always be, Hardin. But is he really the deep, thoughtful guy Tessa fell madly in love with, or has he been a stranger all along? She wishes she could walk away. It's just not that easy. Not with the memory of the passionate nights they spent together. Still, Tessa's not sure she can endure one more broken promise. She's focused on her studies and just starting an exciting new internship at Vance Publishing. She's also being pursued by Trevor, a handsome new co-worker who is exactly the kind of guy she should be with. Hardin knows he made a mistake, possibly the biggest one of his life. He wants to right his wrongs and overcome his demons. He's not going to lose Tessa without a fight. But can he change? Will he change, for love?